2004
DOI: 10.1007/s11172-005-0177-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of suspensions of single-wall carbon nanotubes in polyaniline solutions in N-methylpyrrolidone in UV—Vis—NIR regions

Abstract: Stable suspensions of carbon nanoparticles in polyaniline solutions in N methylpyrrolidone were compared with the suspensions in aqueous solutions of cetyltrimethylammonium bro mide using spectrophotometry in UV-Vis-NIR regions. Polyaniline in low concentrations in N methylpyrrolidone was found to be a more efficient surfactant than cetyltrimethylammonium bromide in water. Analysis of the optical spectra of suspensions of carbon soots in solutions of the polymer made it possible to reveal a noticeable change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These techniques are not general and are susceptible to measurement noise. UV−vis has also been used to study the effect of relevant parameters in SWNT production , and dispersion processes. , It was shown , that there is a limited contribution to the absorption by the carbonaceous impurities left from the CNT production process at wavelengths <600 nm. As for the metal catalyst, both Ni and Y nanoparticles exhibit continuous absorption across the UV−vis range without distinct absorption bands. , Moreover, it was also shown that most of the impurities are removed by the centrifugation and thus their actual contribution to the spectrum is negligible …”
Section: The Choice Of Dispersantmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques are not general and are susceptible to measurement noise. UV−vis has also been used to study the effect of relevant parameters in SWNT production , and dispersion processes. , It was shown , that there is a limited contribution to the absorption by the carbonaceous impurities left from the CNT production process at wavelengths <600 nm. As for the metal catalyst, both Ni and Y nanoparticles exhibit continuous absorption across the UV−vis range without distinct absorption bands. , Moreover, it was also shown that most of the impurities are removed by the centrifugation and thus their actual contribution to the spectrum is negligible …”
Section: The Choice Of Dispersantmentioning
confidence: 99%
“…These techniques are not general and are susceptible to measurement noise. UV-vis has also been used to study the effect of relevant parameters in SWNT production 19,20 and dispersion processes. 21,22 It was shown 23,24 that there is a limited contribution to the absorption by the carbonaceous impurities left from the CNT production process at wavelengths <600 nm.…”
mentioning
confidence: 99%
“…Conductivity in polyaniline occurs along the main chain, statistically arranged perpendicular to the nanotubes (at the ‘core-shell’ structure), which may give interesting effects resulting from the spatial orientation of the nanotubes. Vitreous polyaniline can be easily crushed and combined as dry blends with other polymers in order to facilitate the processing or refinement of the material [ 152 , 153 ]. Covering the nanotube completely with polymer is difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Such an agent can be nonionic surfactant or co-polymerizable monomer. Non-ionic surfactants additionally increase the degree of nanotube dispersion, supporting the breakdown of their aggregates [ 149 , 151 , 153 , 154 ].…”
Section: Resultsmentioning
confidence: 99%
“…After the CNTs have been detached from aggregates, there is a possibility of re-agglomeration. To stabilize the system in water based dispersions, different types of surfactants such as ionic (anionic and cationic), non-ionic, polymer based and their combinations have been used comprising current state-of-the-art [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . The basic idea is to enable surfactant molecules to be adsorbed on the surface of CNTs via hydrophobic interactions, π - π bonds, hydrogen bonds or electrostatic interactions [29] , [30] .…”
Section: Introductionmentioning
confidence: 99%